Study of the effect of acid nature on the leaching process of the sinter of nepheline syenites of the Sandyk deposit (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The elemental composition of solid insoluble residues obtained by decomposition of nepheline syenites by sintering using potassium carbonate and subsequent leaching with nitric and sulfuric acids was studied. It was shown that compounds containing aluminum, iron, alkaline, and alkaline-earth metals dissolve equally well in both nitric and sulfuric acids. Manganese, lead, and rare-earth metals dissolve better in nitric acid, while strontium and titanium compounds dissolve better in sulfuric acid. The possibility of aluminum and iron precipitation at pH=5 from a nitric acid solution and the production of metal oxides with an aluminum content of 80.6% and an iron content of 19.1%, as well as rare-earth metals with an content of 0.15%.
Keywords: nepheline syenites, sintering, potassium carbonate, solid insoluble residue, nitric acid, sulfuric acid, aluminum, iron, and rare-earth metals